2020
DOI: 10.1002/anie.202011588
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Energy Density of Aqueous Batteries via Facile Grotthuss Proton Transport

Abstract: The recent developments in rechargeable aqueous batteries have witnessed a burgeoning interest in the mechanism of proton transport in the cathode materials. Herein, for the first time, we report the Grotthuss proton transport mechanism in α‐MnO2 which features wide [2×2] tunnels. Exemplified by the substitution doping of Ni (≈5 at.%) in α‐MnO2 that increases the energy density of the electrode by ≈25 %, we reveal a close link between the tetragonal‐orthorhombic (TO) distortion of the lattice and the diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 41 publications
2
90
2
Order By: Relevance
“…After discharge (i.e., at point #B in the first cycle, and point #H in the second cycle), two diffraction peaks at 16.35° and 33.95° emerge, corresponding well to the monoclinic MnOOH (orthorhombic, Pnma (62), PDF #88-0648), a typical product of proton conversion in MnO 2 [ 40 , 41 ]. Meanwhile, zinc sulfate hydroxide hydrate by-product (Zn 4 (OH) 6 ·ZnSO 4 ·xH 2 O, abbreviated as “ZSH,” PDF #44-0673) is generated upon discharge, featuring a set of strong diffraction peaks located at 8.12°, 15.08°, 21.56°, and 24.57°, which is a critical evidence for proton intercalation into the lattice framework of MnO 2 [ 20 ]. The presence of ZSH on the electrode can be further confirmed by the morphology evolutions of β-MnO 2 @GO electrodes, (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After discharge (i.e., at point #B in the first cycle, and point #H in the second cycle), two diffraction peaks at 16.35° and 33.95° emerge, corresponding well to the monoclinic MnOOH (orthorhombic, Pnma (62), PDF #88-0648), a typical product of proton conversion in MnO 2 [ 40 , 41 ]. Meanwhile, zinc sulfate hydroxide hydrate by-product (Zn 4 (OH) 6 ·ZnSO 4 ·xH 2 O, abbreviated as “ZSH,” PDF #44-0673) is generated upon discharge, featuring a set of strong diffraction peaks located at 8.12°, 15.08°, 21.56°, and 24.57°, which is a critical evidence for proton intercalation into the lattice framework of MnO 2 [ 20 ]. The presence of ZSH on the electrode can be further confirmed by the morphology evolutions of β-MnO 2 @GO electrodes, (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Toward this goal, researchers have adopted various technologies, including pre-intercalation engineering [ 15 ], defect engineering [ 16 , 17 ], interfacial optimization [ 18 , 19 ], and metal-doping [ 20 ], etc. Especially, the incorporation of oxygen vacancies (V O ) is an effective route to improve the rate performance of MnO 2 electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the bond competition between Mn−O and O−H bonds, the electron density of oxygen atoms in Mn−O bonds is increased (Figure 1 c). [12] As a result, the hydrogen bonds between MnO 2 and NH 4 + are enhanced after NH 4 + insertion, which will reinforce the stabilization of distorted Mn 3+ O 6 octahedra in MnO 2 . Therefore, the co‐insertion of H + /NH 4 + ions in MnO 2 would enhance the electrochemical performance of aqueous batteries.…”
Section: Figurementioning
confidence: 93%
“…In the cases of aqueous batteries with NH 4 + ions, the insertion of NH 4 + ions will be beneficial to the structural stability of host materials due to the formation of hydrogen bonds between the inserted NH 4 + ions and the framework of host materials, resulting in the enhanced cycling performance of the batteries [11] . In the aqueous zinc batteries, the active sites of various charge carriers are often varied in the host materials [12] . As a result, H + ions can insert into the host materials accompanied by the insertion of Zn 2+ ions, realizing the co‐insertion of dual cations in the aqueous zinc batteries [8b, 13] .…”
Section: Figurementioning
confidence: 99%
“…Although much progress has been made for COF‐based supercapacitors, it is still challenging to achieve both high energy density and high power density that is related to the transport of ion charge carriers in the electrode. A recent study has shown that proton Grotthuss transfer in inorganic complexes can facilitate the electrode's redox reaction to enable a high rate capability and energy density for electrochemical devices [39, 40] . But, such a discovery has been not reported for organic materials.…”
Section: Introductionmentioning
confidence: 99%